Genome Complexity Reduction High-Throughput Genome Sequencing of Green Iguana (Iguana iguana) Reveal a Paradigm Shift in Understanding Sex-Chromosomal Linkages on Homomorphic X and Y Sex Chromosomes - Koomgun, Tassika; Laopichienpong, Nararat; Singchat, Worapong; Panthum, Thitipong; Phatcharakullawarawat, Rattanin; Kraichak, Ekaphan; Sillapaprayoon, Siwapech; Ahmad, Syed Farhan; Muangmai, Narongrit; Peyachoknagul, Surin; Duengkae, Prateep; Ezaz, Tariq; et al. (Frontiers in Genetics, 2020)
The majority of lizards classified in the superfamily Iguanoidea have an XX/XY sex-determination system in which sex-chromosomal linkage shows homology with chicken (Gallus gallus) chromosome 15 (GGA15). However, the genomics of sex chromosomes remain largely unexplored owing to the presence of homomorphic sex chromosomes in majority of the species. Recent advances in high-throughput genome complexity reduction sequencing provide an effective approach to the identification of sex-specific loci with both single-nucleotide polymorphisms (SNPs) and restriction fragment presence/absence (PA), and a better understanding of sex chromosome dynamics in Iguanoidea. In this study, we applied Diversity Arrays Technology (DArTseq™) in 29 phenotypic sex assignments (14 males and 15 females) of green iguana (Iguana iguana). We confirmed a male heterogametic (XX/XY) sex determination mode in this species, identifying 29 perfectly sex-linked SNP/PA loci and 164 moderately sex-linked SNP/PA loci, providing evidence probably indicative of XY recombination. Three loci from among the perfectly sex-linked SNP/PA loci showed partial homology with several amniote sex chromosomal linkages. The results support the hypothesis of an ancestral super-sex chromosome with overlaps of partial sex-chromosomal linkages. However, only one locus among the moderately sex-linked loci showed homology with GGA15, which suggests that the specific region homologous to GGA15 was located outside the non-recombination region but in close proximity to this region of the sex chromosome in green iguana. Therefore, the location of GGA15 might be further from the putative sex-determination locus in green iguana. This is a paradigm shift in understanding linkages on homomorphic X and Y sex chromosomes. The DArTseq platform provides an easy-to-use strategy for future research on the evolution of sex chromosomes in Iguanoidea, particularly for non-model species with homomorphic or highly cryptic sex chromosomes.